Revitalizing Rural Areas in Malaysia: A Framework for Economic Revitalization. Issue 1 (November 2019) - Rashid, M F; Ngah, I; Misnan, S H
Abstract: Rural, poor and marginalized community often face many challenges in achieving economic equality and attaining socio-economic sustainability, especially among rural communities who have limited sources of income. In countries with emerging economies such as Malaysia, rural populations constitute the majority of citizens. They are generally poorer and more disadvantaged than their urban counterparts. In Malaysia, rural communities and their development are important aspects of a country's political and economic stability in which revitalization of the rural economic is part and parcel of a nation's development. Rural revitalization is an outcome of the interplay between many sources of influence and it is also a response to the opportunities and challenges which are presented by rural decline. This paper provides an overview of revitalization of rural areas. Besides that, it also explains the factors differences in economic performance and socioeconomic differentiation in rural areas in order to achieve a better outcome for rural revitalization. Finally, this paper discusses the framework to revitalize rural areas and the methods to use this framework that measure rural economic performance.